Pathology of the Organs of Vision in Metallurgists - A. L. Onischenko; A. V. Kolbasko; M. A. Melnichenko; S. N. Filimonov (Oftalʹmologiâ, 2019)
The frequency and structure of ophthalmopathology in workers of the Novokuznetsk Metallurgical Combine (NMC) have been studied. In total 1911 workers of NMC have been examined. The control group comprised 1801 people working in hazardous industrial conditions. The experimental group consisted of employees dealing with management, engineering center, accounting (110 people). Their work was not connected with the impact of unfavorable factors of metallurgical production. In the control group, the hazard classes ranged from 3.2 to 3.4. The difference between the classes of hazard impact consisted in an increase of the intensity of the hazardous factors exposure. In the structure of conjunctival diseases we have diagnosed chronic conjunctivitis (198.3 ‰), chronic blepharoconjunctivitis (109.4 ‰), pinguecula (266.7 ‰) and pterygium (7.2 ‰) in metallurgical workers. Pengucules in the control group of workers was not only more often than in engineers, but also larger, often located in the inner and outer corner of the eye, and was detected in workers under 30–35 years. The workers of the main shops suffered more severely from the function of tear production and the stability of the pre-corneal tear film. The miners suffered from the highest frequency of cataract development — 301 ‰. Thus, a high incidence of inflammatory and dystrophic diseases of the eyelids and conjunctiva, cataracts in metallurgy has been established. An increase in the frequency of ophthalmopathology was noted with an increase in the length of service under harmful conditions of metallurgical production. The authors suggest the term “metallurgy ophthalmopathy”, which includes manifestations of chronic conjunctivitis and / or blepharoconjunctivitis against the background of unstable precorneal film and frequent formation of posterior-subcapsular opacities of the lens.